The Fourth International Symposium on Genetic Disorders of the Ras/MAPK pathway. Issue 8 (7th May 2016) - Stevenson, David A.; Schill, Lisa; Schoyer, Lisa; Andresen, Brage S.; Bakker, Annette; Bayrak‐Toydemir, Pinar; Burkitt‐Wright, Emma; Chatfield, Kathryn; Elefteriou, Florent; Elgersma, Ype; Fisher, Michael J.; Franz, David; et al.
Abstract : The RASopathies are a group of disorders due to variations of genes associated with the Ras/MAPK pathway. Some of the RASopathies include neurofibromatosis type 1 (NF1), Noonan syndrome, Noonan syndrome with multiple lentigines, cardiofaciocutaneous (CFC) syndrome, Costello syndrome, Legius syndrome, and capillary malformation–arteriovenous malformation (CM‐AVM) syndrome. In combination, the RASopathies are a frequent group of genetic disorders. This report summarizes the proceedings of the 4th International Symposium on Genetic Disorders of the Ras/MAPK pathway and highlights gaps in the field. © 2016 Wiley Periodicals, Inc.